Electronic Book Piracy in Review of Law Number 28 Year 2014 on Copyright - Deanera, Princessa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Books copyrights supported by technological developments have shifted to digital product. Digital products are products with a non-physical form or usually in electronic form which are usually traded online via internet media. Creative product that have become digital products today are books in the form of e-books. The practice of storing, distributing and utilizing digital product on the internet has become so easy and conducted without paying attention to the copyright protection of the creators. The purpose of research in this journal was to analyze copyright protection against e-book piracy in terms of the Copyright Law and described legal remedies that can be taken for violations of e-book piracy. The type of research used by the author was a type of normative legal research with statutory and conceptual approaches. The legal materials used consist of primary legal materials, namely laws and regulations, judge's decisions, treatises on making laws and secondary legal materials obtained from relevant books, journals, literature, documents and archives through literature research. The results of this study stated that a form of copyright law protection is given because not everyone can create a work that is worthy or that can be enjoyed by humans to the fullest, only certain people can employ their brain's thinking power to then put it into a work so as to produce a useful creation. That's why Copyrights Law grantees an exclusive nature, where only certain people can get these rights.